Elderly Healthy Living Culture Connection Withrheumatic Disease Preventio Efforts Inpelayanan Sosial Elderly And Childrenchildren Area Binjai And Medan - Chairunisa, Milna; Gultom, Heri (Tanjungpura Journal of Nursing Practice and Education, 2022)
Background: Rheumatic disease not only attacks the joints, but also attack organs or other body parts. According to WHO (World Health Organization) estimates that approximately 335 million people worldwide suffer from rheumatic diseases. This number corresponds with the increase of elderly man and a variety of other health factors that are predicted to continue to increase in the future. It is estimated that approximately 25% of patients with rheumatic will experience a disability due to damage to the bone and joint disorders. Objective: aims to determine the relationship of culture of healthy living elderly with Rheumatic disease prevention efforts in UPT social services elderly and young children Binjai "“ Medan. Method: Terrain population in this study as many as 172 people. Based on the results of the bivariate analysis using analytical survey, which uses cross sectional method using primary data. Results indicate that the culture of healthy living in the poor category (7.7%) and (51.3%). Prevention of rheumatic disease in the good category (35.9%) and the results can (p = 0.674 0.05), the Ha is rejected, Ho accepted. Conclusion: This shows there is no significant relationship between culture elderly healthy living and the prevention of rheumatic disease.